Complicated Calcaneal Fracture with Displacement Following Osteosynthesis and Successful Reoperation: A Case Report - Skov, Tobias Bak ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Calcaneal fractures are relatively uncommon but account for a significant proportion of tarsal injuries. Often resulting from high-energy trauma, they carry a high risk of complications and remain a clinical challenge. Although open reduction and internal fixation (ORIF) is often successful, certain risk factors may predispose to failure and unexpected complications. Case Presentation: A 49-year-old female sustained a closed, displaced tongue-type calcaneal fracture after a fall from height and underwent acute screw fixation. At four weeks, radiographs revealed fracture recurrence and hardware failure, necessitating urgent reoperation with realignment and re-fixation, followed by a restrictive postoperative regimen. At 14 weeks post-reoperation, radiographs confirmed fracture healing. Upon completion of the treatment course, the patient was referred for continued physiotherapy to support ongoing functional recovery. Despite slight residual limitations, the patient reported minimal discomfort and regained mobility, reflected in an American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot Score of 81.Discussion: Calcaneal fractures are complex injuries with a high complication rate. Initial fixation of tongue-type calcaneal fractures may fail due to factors such as obesity, age, gender, surgical technique, or inadequate aftercare. A good functional outcome was ultimately achieved through timely reoperation, strict rehabilitation protocols, and close follow-up.Conclusion: This case underscores the importance of early surgical intervention, mitigating risk factors, and structured rehabilitation in managing complex calcaneal fractures. Risk factors should guide both surgical planning and aftercare. Early recognition of fixation failure and reoperation within four to six weeks can still result in favourable outcomes, even in high-risk patients.